2020
DOI: 10.1002/jemt.23540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of total phenol and flavonoid content and antimicrobial and antibiofilm activities of Trollius chinensis Bunge extracts on Streptococcus mutans

Abstract: Dental caries is a chronic disease with multiple bacterial infections, Streptococcus mutans is the main cariogenic bacteria. Trollius chinensis Bunge is a common folk medicine in the Xinjiang area of China. In this study, we investigated the total flavonoid content and total phenol content in four types of T. chinensis Bunge extracts and the inhibitory effects of these extracts on S. mutans. Agar diffusion method was used to measure the inhibition zone diameters, and the minimum inhibitory concentration and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, bacterial biofilm formation is known to increase resistance against the antibiotic and plays a critical role in the pathogenesis of infections ( Banerjee et al, 2020 ). Then, we also examined the effect of Mg-doped MnO 2 nanoflowers on S. mutans biofilm formation by crystal violet staining ( Asgharpour et al, 2019 ; Chan et al, 2020 ; Jiang et al, 2020 ; Song et al, 2020 ), and the results showed the same trend as the MTT assay ( Figure 3B ). In the presence of Mg-doped MnO 2 , the inhibition percentage of biofilm formation was 4.1 ± 1.45% at 100 μg/ml, 21.02 ± 0.49% at 200 μg/ml, 39.86 ± 1.59% at 400 μg/ml, and 51.99 ± 1.18% at 800 μg/ml concentration, respectively, showing a dose-dependent enhanced antibacterial activity and reduced biofilm formation against S. mutans induced by Mg-doped MnO 2 nanoflowers.…”
Section: Resultsmentioning
confidence: 80%
“…Furthermore, bacterial biofilm formation is known to increase resistance against the antibiotic and plays a critical role in the pathogenesis of infections ( Banerjee et al, 2020 ). Then, we also examined the effect of Mg-doped MnO 2 nanoflowers on S. mutans biofilm formation by crystal violet staining ( Asgharpour et al, 2019 ; Chan et al, 2020 ; Jiang et al, 2020 ; Song et al, 2020 ), and the results showed the same trend as the MTT assay ( Figure 3B ). In the presence of Mg-doped MnO 2 , the inhibition percentage of biofilm formation was 4.1 ± 1.45% at 100 μg/ml, 21.02 ± 0.49% at 200 μg/ml, 39.86 ± 1.59% at 400 μg/ml, and 51.99 ± 1.18% at 800 μg/ml concentration, respectively, showing a dose-dependent enhanced antibacterial activity and reduced biofilm formation against S. mutans induced by Mg-doped MnO 2 nanoflowers.…”
Section: Resultsmentioning
confidence: 80%
“…Flavonoids are metabolite compounds that have antibacterial activity, especially against S. mutans and S. dysenteriae. Extracts from several herbs containing flavonoids are known to actively inhibit the growth of S. mutans (Jiang et al, 2020) since they can penetrate the film membrane of S. mutans (Veloz et al, 2019). Flavonoids could form complex compounds with the constituent compounds of the bacterial cell wall (extracellular protein).…”
Section: Resultsmentioning
confidence: 99%
“…The MIC and MBC of AMFE against S. mutans were determined by the microdilution method [ 50 ]. First, a 50 mg/mL solution of AMFE was prepared, which was aseptically filtered and then diluted to a concentration of 50–1 mg/mL using sterile ultrapure water.…”
Section: Methodsmentioning
confidence: 99%